Determination of the essential nutrients required for milk fermentation by Lactobacillus plantarum. (January 2016) - Ma, Chengjie; Cheng, Guojun; Liu, Zhenmin; Gong, Guangyu; Chen, Zhengjun
Abstract: The aim of this study was to investigate the chemically defined nutritional requirements for Lactobacillus plantarum in milk. Twenty amino acids, five nucleotide precursors, ten vitamins, and ten mineral salts were added to skim milk. The selective removal of individual nutrient groups led to the identification of amino acids and nucleotide precursors as essential nutrients for L. plantarum growth. Mineral salts were not essential but had a growth-stimulating effect on L. plantarum . Further single-omission growth experiments revealed six key amino acids (isoleucine, leucine, valine, tyrosine, methionine, and phenylalanine) and at least one purine required as minimal nutrient for L. plantarum growth in milk. L. plantarum grew and propagated well in the fortified milk supplementation with six amino acids and adenine. The pH values of the fortified milk fermented using L. plantarum ST-III, WCFS1 and LPHS were 3.93, 3.84 and 4.02 at 72 h, respectively. However, the pH values of the control-fermented milk using L. plantarum ST-III, WCFS1 and LPHS were only 5.73, 5.61 and 5.84 at 72 h. The identification of the chemically defined requirements for growth of L. plantarum in milk without complex and undefined substances contributes to the understanding of the physiological properties and metabolic pathways of bacteria. Highlights: Amino acids and nucleotides are essential for milk fermentation by Lactobacillus plantarum . Six amino acids and one purine were identified as minimal nutrient for L. plantarum . L. plantarum strains grew and propagated well in the fortified milk. Chemically defined identification contributes to the understanding of the bacteria. L. plantarum could not convert caseins into free amino acids in milk.